ANALISIS KEBUTUHAN TENAGA KERJA REKAM MEDIS UNIT RAWAT JALAN DENGAN METODE WISN DI RUMAH SAKIT SITI MIRIAM LAWANG - Septya Anggari Salsa Hari Sukma; Achmad Jaelani Rusdi; Retno Dewi Prisusanti (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2023)
The WISN (Workload Indicator Staffing Needs) method, functions as a calculation in the needs of human resources (HR) by using the workload by health human resources in all work units in service facilities. The registration officer is in charge of serving patients, besides that the cashier also helps to serve the registration. The activities carried out not only serve registration, but also concurrently filing and cashier. The purpose of this study is to analyze the needs of medical record personnel in the URJ registration section at Siti Miriam Lawang Hospital with 5,863 patients in 2021. A descriptive type of research with a quantitative approach, a sample and population of URJ registration officers, using a cross sectional approach. using data collection and counting staff needs. Based on the results observation and calculation of WISN, the results were obtained that there should be additional officers so that the service was maximized and in accordance with the tupoksi.